2018
DOI: 10.1161/circoutcomes.118.004951
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Missing Stroke Severity Data on the Accuracy of Hospital Ischemic Stroke Mortality Profiling

Abstract: Background: The Centers for Medicare and Medicaid Services have proposed 30-day ischemic stroke risk-standardized mortality rates that include adjustment for stroke severity using the National Institute of Health Stroke Scale (NIHSS), which is often undocumented. We used simulations to quantify the effect of missing NIHSS data on the accuracy of hospital-level ischemic stroke risk-standardized mortality rate profiling for 100 hypothetical hospitals with different case volumes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Large amounts of missing data may have introduced bias particularly if the proportion of missing cases varied between hospitals, indicating differential bias in severity ascertainment. A recent publication has reported that missing severity data leads to inaccuracies in outlier classification, although residual bias remained, particularly for smaller hospitals [41]. Our severity measure is less prone to selective assessment with the advantage of maximising available cases for analysis (and therefore power), and minimizing differential ascertainment.…”
Section: Discussionmentioning
confidence: 99%
“…Large amounts of missing data may have introduced bias particularly if the proportion of missing cases varied between hospitals, indicating differential bias in severity ascertainment. A recent publication has reported that missing severity data leads to inaccuracies in outlier classification, although residual bias remained, particularly for smaller hospitals [41]. Our severity measure is less prone to selective assessment with the advantage of maximising available cases for analysis (and therefore power), and minimizing differential ascertainment.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline data were collected prospectively using an electronic data capture system by face‐to‐face interviews, which included age, sex, ethnicity, region (North, Northeast, East, Central South, and West), hospital level (grade Ⅱ and grade Ⅲ), family income, education level, symptom to admission (<24 or ≥24 hours), intravenous thrombolysis and endovascular treatment, body mass index (calculated as weight in kilograms divided by height in meters squared, kg/m 2 ), current smoking, heavy drinking (≥2 standard alcohol consumption per day), medical history (stroke, coronary heart disease, hypertension, or diabetes), stroke type (TIA and IS), the causative subtypes of IS classified according to the TOAST (Trial of Org 10172 in Acute Stroke Treatment) criteria, 25 severity of stroke on admission (National Institutes of Health Stroke Scale score), 26 systolic blood pressure (SBP) at admission, high‐density lipoprotein cholesterol (HDL‐C), low‐density lipoprotein cholesterol (LDL‐C), triglyceride, fasting blood glucose (FBG) at admission, and discharge medications (antiplatelet, lipid‐lowering, 27 and antihypertensive drugs).…”
Section: Methodsmentioning
confidence: 99%
“…Open access weight in kilograms divided by height in metres squared, kg/m 2 ), medical history (hypertension, diabetes mellitus, dyslipidaemia, stroke or TIA, atrial fibrillation or flutter, peripheral vascular disease, heart failure, chronic obstructive pulmonary disease (COPD)), stroke type (ischemic stroke or TIA), aetiology classification of ischaemic stroke performed according to the TOAST (Trial of Org 10172 in Acute Stroke Treatment) criteria, 11 current smoker, in-hospital medication (cholesterol-lowering agents, antihypertensive agents, hypoglycaemic agents, antiplatelet agents and anticoagulant agents), severity of stroke on admission (National Institutes of Health Stroke Scale, NIHSS), 12 time from onset of symptoms to admission, total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, triglyceride, fasting blood glucose, estimated glomerular filtration rate calculated using the creatinine-based Chronic Kidney Disease Epidemiological Collaboration equation 13 and highsensitivity C reactive protein (hs-CRP), and medication on discharge (cholesterol-lowering agents, antihypertensive agents, hypoglycaemic agents, antiplatelet agents and anticoagulant agents).…”
mentioning
confidence: 99%